Agathiyar kuzhambu (herbo-mineral siddha formulation) - Rakulini, R.; Sounthararajan, K.; Sundararajan, S. (International Ayurvedic Medical Journal, 2021)
Introduction: Agathiyar kuzhambu (A.k) is a herbo-mineral siddha formulation. It is explained in the Siddha Vaith iya Thiraddu Book. In Siddha Medicine, there are 32 internal & external medicines are explained in the Siddha Literatures. Agathiyar kuzhambu is a one form of the internal medicine which is commonly used in purgation ther apy. It contains 11 ingredients. Agathiyar kuzhambu has different herbo- mineral ingredients which are having wide range of therapeutic uses. It is commonly used in Siddha OPDs. Aim: The researcher is going to develop the documentary evidence for the effectiveness of Agathiyar kuzhambu. Results and Discussion: Six ingredients herbs have hot potency and Pungent efficacy. These have many pharmacological actions. Commonly, these ingredients are possessed antioxidant, anti-microbial, hepatoprotective, anti-inflammatory, anti-fungal, anthelmintic, anti-dia betic and anti -hypertensive activity. In Siddha, these ingredients and 5 minerals and metals ingredients were used in many disease conditions. Lots of adjuvants of Agathiyar kuzhambu have hot potency and pungent efficacy. Some of adjuvants have cool potency and sweet efficacy. In Siddha, these adjuvants were used in many disease conditions. Conclusion: According to the above study, Agathiyar kuzhambu may be act as stimulant and osmotic purgative at the same time it can use as a treatment aspect of many diseases. This study gives documentary evidence of Agathiyar kuzhambu as a purgative & possess many pharmacological activities in Siddha medicine.
Keywords: Agathiyar kuzhambu; Siddha Medicine; Purgative; Croton tiglium